2014
DOI: 10.3389/fimmu.2014.00400
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Delta T-lymphocytes in Hepatitis C and Chronic Liver Disease

Abstract: Discovered 30 years ago, gamma delta (γδ) T-lymphocytes remain an intriguing and enigmatic T-cell subset. Although in humans they comprise a small fraction of the total circulating T-lymphocyte pool, they represent an important T-cell subset in tissues such as the liver, with roles bridging the innate and adaptive immune systems. The associations of γδ T-lymphocytes with chronic liver disease have been explored – however, there remain conflicting data as to whether these T-cells are pathogenic or protective. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 82 publications
1
52
0
Order By: Relevance
“…Thus, the liver functions as a second 'firewall', clearing commensals from the portal circulation where intestinal defenses are overwhelmed, 1 and is enriched with a number of innate immune cells, including Kupffer cells (liver‐resident macrophages), natural killer (NK) cells and innate‐like T cells. In the human liver, mucosal‐associated invariant T cells (MAIT) cells are the most dominant population of innate‐like T cells, comprising up to 50% of all T cells in the liver, 2 which is in contrast to invariant NKT cells (iNKT; ~1%) and γδ T cells (~15%) 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the liver functions as a second 'firewall', clearing commensals from the portal circulation where intestinal defenses are overwhelmed, 1 and is enriched with a number of innate immune cells, including Kupffer cells (liver‐resident macrophages), natural killer (NK) cells and innate‐like T cells. In the human liver, mucosal‐associated invariant T cells (MAIT) cells are the most dominant population of innate‐like T cells, comprising up to 50% of all T cells in the liver, 2 which is in contrast to invariant NKT cells (iNKT; ~1%) and γδ T cells (~15%) 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…In the human liver, mucosalassociated invariant T cells (MAIT) cells are the most dominant population of innate-like T cells, comprising up to 50% of all T cells in the liver, 2 which is in contrast to invariant NKT cells (iNKT;~1%) and γδ T cells (~15%). 3,4 The invariant T-cell receptor (TCR) rearrangement of MAIT cells, Vα7.2-Jα33, was first identified during an extensive analysis of the TCR repertoire of human CD4 − CD8 − (double-negative; DN) T cells, Porcelli et al 5 and subsequently shown to be characteristic of a novel population restricted by the non-polymorphic and highly evolutionarily conserved major histocompatibility complex (MHC) class Ib molecule, MHC class I-related protein 1 (MR1). 6,7 The relative abundance of Vα7.2-Jα33 transcripts in human gut biopsies, as well as the enrichment of homologous Vα19-Jα33 transcripts among murine lamina propria lymphocytes compared with intraepithelial lymphocytes or mesenteric lymph nodes, 7 led to this population being called MAIT cells.…”
Section: Introductionmentioning
confidence: 99%
“…They are the major subset of γδ T cells in human blood and can comprise between 1–10% of total blood T cells in healthy humans [59]. These cells are also found at high frequency in the gut, liver and other mucosal tissues [6063]. Vγ9Vδ2 T cells respond potently to certain tumor cells [64, 65] and to microbial pathogens such as Mycobacterium tuberculosis and leprae [66] and are thus a population of great interest for immunotherapeutic manipulation.…”
Section: Vγ9vδ2 T Cell Activation By Phosphoantigensmentioning
confidence: 99%
“…The expression of CD161 has been widely studied. It has been described on the vast majority of NK cells 25 , on different innate-like T cell subset,s such as NKT cells 3 , mucosal-associated invariant T (MAIT) cells 26 , γδ T cells 27, 28 and in other T cell subgroups, both in the CD4+ and CD8+ compartments. CD161 defines cell populations with shared transcriptional and functional features across different human T cell lineages 8 .…”
Section: Discussionmentioning
confidence: 99%